Analisis Determinan Keputusan Investasi Mahasiswa dalam Perspektif Theory Of Planned Behavior: Tinjauan Literatur - Ramadanis Ramadanis; Melati Melati; Natasya Rohel; El Hadji Diouf; Tiara Nurrohim; Elviana Elviana; Bunga Gempita Sari (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
The surge in young investors in the country indicates that university students are increasingly drawn to the financial markets. Unfortunately, the soundness of students' investment choices often lacks a foundation of clear reasoning, as they remain swayed by social influences, limited insight, and the rapid technological advancements that facilitate access to investment opportunities. This study aims to unravel the determinants of students' investment decisions through the lens of the Theory of Planned Behavior (TPB), focusing on financial literacy, risk tolerance, and technology—three factors frequently examined in existing literature. A qualitative approach was adopted, involving a literature review of scholarly articles published between 2020 and 2024. Data gathered from relevant academic sources were analyzed using content analysis techniques to identify research patterns, conceptual relationships, and the consistency of prior findings. The results reveal that the Theory of Planned Behavior effectively explains students' investment decisions through the interplay of attitudes, subjective norms, and perceived behavioral control. Financial literacy emerges as the most robust and consistent determinant influencing investment decisions; risk tolerance shapes investment preferences; and technology acts as a catalyst, enhancing accessibility and convenience. These findings suggest that deepening financial literacy—supported by optimal technology use and adequate risk awareness—can empower students to make investment decisions that are rational, well-calculated, and long-term oriented.